2012
DOI: 10.1177/0961203312467668
|View full text |Cite
|
Sign up to set email alerts
|

Lupus nephritis and non-Hodgkin lymphoma simultaneously diagnosed in a patient on methimazole

Abstract: A 78 year old white male on methimazole due to Grave's thyroiditis presented with acute renal failure after a short term history of progressive shortness of breath, malaise, myalgias, arthralgias, and bilateral lower limb swelling. The abdomen was remarkable for splenomegaly and lower extremities for erythema nodosum. No peripheral lymphadenopathy was detected. Serum albumin was 1.7 g/dl and very high erythrocyte sedimentation rate. Urine sediment was very active with dysmorphic red blood cells and casts and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Frequencies of visits for neoplasm were also elevated in patients during the pre-SLE period. Patients with SLE had elevated risk for developing cancer late in the diseases course [32] and a concordance development of the SLE and cancer has also been reported [33]. Moreover, the ICD-9-CM codes for neoplasm (140–239) contain not only malignant tumors but also benign tumors.…”
Section: Discussionmentioning
confidence: 89%
“…Frequencies of visits for neoplasm were also elevated in patients during the pre-SLE period. Patients with SLE had elevated risk for developing cancer late in the diseases course [32] and a concordance development of the SLE and cancer has also been reported [33]. Moreover, the ICD-9-CM codes for neoplasm (140–239) contain not only malignant tumors but also benign tumors.…”
Section: Discussionmentioning
confidence: 89%
“…The of crescentic induction of glomerulopathy associated with ANCA (Anti-Neutrophil Cytoplasmic Antibody), especially by anti-myeloperoxidase antibodies (MPO-ANCA) [22], has been proposed as one of the possible pathogenic mechanisms of kidney injury due to methimazole use [23]. Furthermore, there is a case of a patient who developed lupus nephritis due to systemic lupus erythematosus presumably induced by methimazole use [24]. The exact mechanism that mediates the injury of methimazole in MCD are unknown; one possibility is a direct damage in the podocyte and in the base membrane [21].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic lupus erythematosus (SLE) is an autoimmune disease characterized by multisystem organ involvement, heterogeneity of clinical features, and a variety of degrees of severity, of which lupus nephritis is constituted with one of the most common causes of morbidity and mortality. However, previous studies showed that SLE could be secondary to infections, hematological malignancies, solid tumors, drugs, and so on (2), with renal involvement (3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature indicated that lupus-like syndrome could be caused by infections, hematological malignancies, solid tumors, and so forth ( 2 ). However, renal involvement presented as lupus nephritis is rare ( 3 7 ). In this research, we describe a rare case of mixed proliferative and membranous lupus nephritis, secondary to mantle cell lymphoma, and partially recovered after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%